Medan Magnet Peralatan Listrik dan Pengaruhnya Terhadap Kesehatan. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan UGM, 1999)
ABSTRACT Health debate on the possible impact of electric and magnetic fields to human began in the 1970's. Since then, many lajor scientific studies have been undertaken into the effect of electric and magnetic fields. This research investigates magnetic fields produced by household and industrial equipment and magnetic fields that xist below transmission lines. The result of investigation shows that the magnetic fields produced by household equipment nd magnetic fields below transmission line will not affect human healths. On the other hands, some of industrial quipments produce magnetic fields that may harm the human body if he or she is exposed to such a high field more than 2 ours everyday.